Kanoniczna forma zawarcia małżeństwa w świetle Kodeksu Kanonów Kościołów Wschodnich - Hołubowicz, Rafał (Ius Matrimoniale, 2013)
Marriage agreement, which is the cause of marriage itself, expressed by betrothed at the moment of contracting it, is not only the act coming from natural law or entirely the sacramental act, but also, due to its particular character both religious and social, it is the act of law that causes concrete, serious consequences. That is the reason why marriage agreement is put under many legal regulations, which precisely define the canonical form of marriage contraction. The issue of canonical form of marriage contraction is still being disputed very intensely by canonists, concerning doctrinal aspects as well as practical side of this problem. Most of existing in this area problems, are related to Church rights and powers in this field, on the one hand, and state power over the institution of marriage, on the other hand; as well as to prerogatives owned by many churches or religions concerning this subject. Particularly difficult matter is validity of marriages, contracted according to norms of different legislation than its own or contracted in rite different than own Church sui iuris. That is the reason, why undertaking a legal reflection over the norms concerning canonical form of marriage contraction, which occur in canons 828-842 of Codex canonum Ecclesiarum Orientalium, seems to be interesting. The first part of this stadium composes the short historical outline of developing the form of ecclesiastical marriage contraction, both on the East and West. Yet in this part, the sense of East tradition for mystical and spiritual aspects of marriage, is clearly pointed out, which will later affect boldly on current legal regulations in East Catholic Churches. It is even visible in the first canon, article six, where role and meaning of so called ritus sacer is outlined, at the time of contracting a marriage. In the Latin Church, the sacrament of marriage essence is identical with its substance, in different words with its sacramental sign. And that is the reason why expressing the marriage agreement proclaimed by its sides, is the sacrament of marriage essence. According to this, the priest is only an official witness of the marriage contraction. In the East- tradition Churches, that issue is different from our way of thinking. The priest himself is the one, who, in the name of God, grants the sacrament to the betrothed and then blesses the marriage contracted that way. Based on this elementary difference in understanding relevant part of canonical marriage form, east legislation adjusts the issue concerning normal minister of marriage as well as the extraordinary one; matters regarding delegation of the power needed for giving blessings to those who are married; things referring to dispensation from canonical form of marriage contraction; norms concerning the form of celebrating this sacrament in special ways or rite in which that celebration is being performed. All these regulations, that have been talked in details hereby, serve a purpose to protect the institution of marriage, which is the basic cell of social organization and also to stress the sacramental character of marriage, contracted between those who were baptized.